Perennial flower strips can be a cost‐effective tool for pest suppression in orchards - Howard, Charlotte; Burgess, Paul J.; Fountain, Michelle T.; Brittain, Claire; Garratt, Michael P. D. (Wiley, 2025)
Flower strips can provide many economic benefits in commercial orchards, including reducing crop damage by a problematic pest, rosy apple aphid (Dysaphis plantaginea [Passerini]). To explore the financial costs and benefits of this effect, we developed a bio‐economic model to compare the establishment and opportunity costs of perennial wildflower strips with benefits derived from increased yields due to reduced D. plantaginea fruit damage under high and low pest pressure. This was calculated across three scenarios: (1) a flower strip on land that would otherwise be an extension of the standard grass headland, (2) a flower strip on land that could otherwise be used to produce apples and (3) a flower strip in the centre of an orchard. Through reduction of D. plantaginea fruit damage alone, our study shows that flower strips on the headland can be a positive financial investment. If non‐crop land was not available, establishment of a flower strip in the centre of an orchard, instead of the edge, could recoup opportunity costs by providing benefits to crops on both sides of the flower strip. Our study can help guide the optimal placement of flower strips and inform subsidy value for these schemes.
Special Focus: The Role of Agricultural Trade in Countering the Effects of Extreme Weather
Keywords: bio-economic model; cost–benefit; crop damage; financial analysis; flower margin; pest control; yield